The Relationship between Factors Influencing and Cybersecurity Awareness among Youth Internet Users in Johor - Lim, Jia Xuan; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2026)
Cybersecurity has become an increasingly critical issue in today’s digital landscape. The rise in cybercrime is largely attributed to a lack of awareness and knowledge among internet users. This study aims to identify the level of factors (response efficacy, self-efficacy, perceived threats) influence cybersecurity awareness among youth internet users in Johor and identify the level of cybersecurity awareness among youth internet users in Johor. Furthermore, in this study, the researcher also examines the relationship between factors (response efficacy, self-efficacy, perceived threats) and cybersecurity awareness among youth internet users in Johor, Malaysia. The target population consists of approximately 4,009,670 youth internet users in Johor. To obtain a representative sample, the Krejcie and Morgan table was used to determine sample sizes of 384 participants. A quantitative research design was adopted, with data collected through an online survey administered via Google Forms. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings showed that there are significant relationships between factors (response efficacy, self-efficacy, perceived threats) and cybersecurity awareness among youth internet users in Johor. Based on the findings, this study intends to offer practical recommendations to enhance cybersecurity awareness and reduce the risk of cybercrime among internet users.